AN INVESTIGATION OF ANXIETY MANIFESTATION AND COPING MECHANISM USED BY THE UNIVERSITY STUDENTS IN SPEAKING EFL CLASSROOM - wati, atikah; larasaty, gina (Wiralodra English Journal, 2020)
This study focuses on the manifestation of speaking anxiety and the coping mechanism that used by the second semester of university students. Young (1991) claimed that anxiety may affect the quality of an individual’s communication or willingness to communicate. Students with anxiety show a passive attitude in their studies such as low motivation in learning and poor in performances and examination. Thus, this study used a descriptive qualitative approach, the data collection was carried out through observation and interview adopted from (Hadziosmanovic, 2012). There were 6 students who are belong to different levels of anxiety participated in this study. The result showed that students experienced hearth racing, dry throat and mouth, muscle twisted, trembling hands, embarrassed, and nervous feeling which belong to physiological manifestation, 3 students experienced lost the words and could not find the right vocabularies in English that leads to switched the language use which belong to linguistic manifestation. In coping mechanism, reminiscence, relearning, and remediation were used by the students. However, only 2 students learn to re-experiencing their previous experiences for the successful performances. Future researches may considered the anxiety manifestation and its coping mechanism in online learning.